Western Boundary of the North Atlantic Subtropical Gyre: Decadal Change - Santana Toscano, Daniel (2020)
The A20 is a meridional hydrographic section located at 52ºW on the western North Atlantic Subtropical Gyre that encloses the main paths of the Atlantic Meridional Overturning Circulation (AMOC). Using data from two A20 hydrographic cruises carried out in 2003 and 2012 together with LADCP data and the velocities from an inverse box model, the circulation of the western North Atlantic Subtropical Gyre is estimated. The main poleward path of the AMOC is the Gulf Stream (GS) which carries 129.0±10.5 Sv in 2003 and 110.4±12.2 Sv in 2012. Due to the seasonality, the GS position is shifted southward in 2012 - relative to that of 2003 - as the cruise took place in Spring. In opposite direction, the Deep Western Boundary Current (DWBC) crosses the section twice, first at 39.3-43.2ºN (-34.9±7.5 Sv in 2003 and -25.3±9.4 Sv in 2012) and then at 7.0-11.7ºN (42.0±8.0 Sv in 2003 and 48.0±8.1 Sv in 2012). Two zonal currents contribute with westward transports, the North Equatorial Current at ca. 18ºN (-5.2±3.8 Sv in 2003 and - 4.7±3.1 Sv in 2012) and the North Brazil Current on the southern edge of the section (- 22.8±1.63 Sv and -32.0±1.80 Sv for 2003 and 2012, respectively). Máster en Oceanografía 2019-2020